Bio-inspired Computing for Network Modelling - N. Rajaee; A. A. S. A Hussaini; A. Zulkharnain; S. M. W Masra (Journal of Advanced Research Design, 2023)
In this paper, we propose an approach to model and simulate a network problem using bio-inspired computing. Information in a network is embedded in DNA sequence strands and in-vitro implementation is proposed via bio-molecular tools such as hybridization, ligation and polymerase chain reaction. The output of the computation is derived from gel electrophoresis process.